ALGEBRAIC STRUCTURES IN THE SPACES OFLIPSCHITZ FUNCTIONS - Martsinkiv, M. V.; Samiliv, I.-A. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
The algebra of Lipschitz functions of the metric space and their scalar homomorphisms are studied in this paper, using free Banach spaces.